A Criminological Review of The Role of Village Heads in Crime Prevention and Control (A Study in Kapringan Village, Indramayu Regency) - Durma Durma; Sanusi Sanusi (Riviera Publishing, 2026)
Kapringan Village, Krangkeng District, Indramayu Regency, as part of a rural community subject to ongoing social and economic dynamics, is not insulated from the problem of crime. Crime in rural areas is a social phenomenon influenced by various factors and requires an active role from the village government — particularly the village head — in maintaining public order and security. This research aims to determine the role of the village head from a criminological perspective in the prevention and control of criminal acts in Kapringan Village, Krangkeng District, Indramayu Regency. The issues examined include the factors that cause crime and the efforts made by the village head in preventing and addressing crime within the area, viewed through a criminological lens. The research employs a qualitative approach that describes the reality of crime in Kapringan Village, utilizing an empirical legal research framework from a criminological perspective, with data gathered through interviews and field observations as well as relevant laws, regulations, and literature. The findings reveal that the factors contributing to crime in Kapringan Village include economic hardship, low levels of education, unemployment, the influence of the social environment, and weak legal awareness within the community. The village head's efforts in preventing and addressing crime encompass coordination with security forces (TNI, Polri) and community leaders, environmental security coaching, legal counseling, and community empowerment through social and economic activities. This research is expected to offer insights for village heads and government officials in fostering public security and order in a sustainable manner.